2006
DOI: 10.1111/j.1464-5491.2006.01868.x
|View full text |Cite
|
Sign up to set email alerts
|

Social consumption of alcohol in adolescents with Type 1 diabetes is associated with increased glucose lability, but not hypoglycaemia

Abstract: In an uncontrolled, social context, moderately heavy alcohol consumption by adolescents with Type 1 diabetes appears to be associated with increased glycaemic variation, but not with low glucose levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 8 publications
0
50
0
1
Order By: Relevance
“…The choice of the time difference, n, will depend on the clinical question being addressed. CONGA has been subsequently used in studies investigating both type 1 and type 2 diabetes [36][37][38]. CONGA has the benefits of being highly reproducible and able to be adjusted for varying time intervals depending on the specific issue being addressed.…”
Section: Continuous Overlapping Net Glycaemic Action (Conga)mentioning
confidence: 99%
“…The choice of the time difference, n, will depend on the clinical question being addressed. CONGA has been subsequently used in studies investigating both type 1 and type 2 diabetes [36][37][38]. CONGA has the benefits of being highly reproducible and able to be adjusted for varying time intervals depending on the specific issue being addressed.…”
Section: Continuous Overlapping Net Glycaemic Action (Conga)mentioning
confidence: 99%
“…Alcohol intake may also result in neglecting diabetes self-care – not measuring glycemia, omitting insulin doses and also involvement in risky behavior [68, 69]. These have an adverse influence on metabolic control and the course of disease, including glycemic instability and increased risk of DKA [70]. It is worth noting that moderate consumption of wine is not prohibited, and may have beneficial vascular effects in diabetes [71].…”
Section: Alcohol and Illicit Drugs Intakementioning
confidence: 99%
“…For example, one study found that moderately heavy alcohol consumption by adolescents with type 1 diabetes in a social setting (mean of 9 drinks for males, 6 for females—along with meals, sweetened mixers, and dancing) was associated with increased glycemic variation but not with hypoglycemia. 11 In adults with type 1 diabetes, consumption of alcohol has been linked with a greater number of hypoglycemic episodes the following day, 12,13 as well as impaired ability to recognize symptoms of hypoglycemia, a potentially serious outcome. 13 Results from these studies should be interpreted with caution, however, because of the small sample sizes (N = 10–17); more research is still needed to determine the patterns of alcohol use in adolescents with type 1 diabetes and the effects on self-management and blood glucose.…”
Section: Substance Usementioning
confidence: 99%